Adopting a Florida-Friendly Landscape: Steps for Converting a Typical Development Landscape to a Florida-Friendly Landscape - Gail Hansen de Chapman; Jennifer Ramos; Elizabeth A. Felter; Celeste White (EDIS)
ENH-1135, a 15-page illustrated fact sheet by Gail Hansen, Jennifer Ramos, E.A. Felter, and Celeste White, lays out a process of incorporating more trees and plants in three phases, to make a traditional development landscape more environmentally sound and Florida-Friendly. Includes references. Published by the UF Department of Environmental Horticulture, August 2009.